Proposal of peer mentoring model in university environments - Alonso-García, Miguel Aurelio (2021)
In addition to the high number of mentoring publications, there are difficulties in determining the factors that contribute to the success of mentoring. In the present paper, a systematic review is carried out on the variables that have been used as predictors or antecedents, the process variables and the results in the peer mentoring studies in university environments.Most of the time, the programs are aimed at incoming students (mentees), who are accompanied by another's students (mentors) of higher levels, who facilitate their integration.  The review allows proposing a systemic and multilevel model that relates the three types of variables and is intended to be useful to determine the characteristics that peer mentoring programs must have in a university environment from a social point of view; organizational, group and individual; the activities to be carried out in the mentoring meetings; and the different variables in which mentoring can have an impact such as abandonment rates, student integration, career satisfaction, health, etc.